Digital Twin Enables Rational Design of Ultrahigh‐Power Lithium‐Ion Batteries (Adv. Energy Mater. 1/2023). Issue 1 (6th January 2023) - Zhang, Huimin; Ren, Dongsheng; Ming, Hai; Zhang, Wenfeng; Cao, Gaoping; Liu, Jianhong; Wang, Li; Song, Junliang; Qiu, Jingyi; Wang, Jingliang; He, Xiangming; Zhang, Hao
Abstract : Digital Twins In article number 2202660, Dongsheng Ren, Jingyi Qiu, Jingliang Wang, Xiangming He, Hao Zhang, and co‐workers propose a digital twin‐based approach for rational design of ultrahigh‐power LiFePO4 /graphite lithium‐ion batteries. Model‐driven optimization of ultrahigh‐power LiFePO4 /graphite batteries is successfully realized, aiming at the critical factors in the rate‐determining steps. The battery shows a high energy density of 92.38 Wh kg −1 at an ultrafast discharging current of 50 C and can withstand 150 C pulse discharging.